Self-care of caregivers for people with neurological disorders at a philanthropic institution (Research, Society and Development, 2024)
Objective: To analyze the self-care process of caregivers of people with Neurological Disorders at a philanthropic institution. Methodology: exploratory and descriptive research of a qualitative nature, theoretically based on the concept of humanization of health. It was carried out with 15 caregivers of people with neurological disorders, data collection was through semi-structured interviews and 6 workshops at that institution. After collection, thematic analysis was carried out, based on the content analysis technique proposed by Bardin. It was approved by the ethics and research committee with n° 6.501.608. Results: 100% of the participants were female, these caregivers understand that they need to take care of themselves in order to take care of their children, but they report a lack of time, as they do not have an effective support network to assist with issues necessary to carry out their self-care. Conclusion: The study data made it possible to understand the need for greater assistance to these caregivers. Highlighting the importance of providing information on the topic, where health education in the form of workshops, conversation circles and fairs is a means of raising awareness and developing a sense of responsibility for health and self-care. We also point out the need to promote teaching, research and extension with the contribution of studies on the topic, especially a support network. We make it clear that this study does not end here, as it is a topic that still has many dilemmas to be researched, discussed and resolved, in order to promote a better quality of life for caregivers.